Bodily dimensions of reading and writing practices on paper and digitally. Issue 4 (November 2015) - Taipale, Sakari
Highlights: The bodily aspects of reading/writing practices are investigated in Finland. The paper is considered more adaptive to varied reading purposes than the screen. Handwriting is described as a more flexible and relaxed practice than typing. Skills determine less than materials and images the practices of reading/writing. Digital interfaces determine the ways we read and write less than suggested. Abstract: This article investigates the different shapes in which reading and writing practices occur when paper/pen are compared with keyboard/screen. The focus is on the bodily aspects of these practices. Reading and writing are viewed as techniques of the body, which over the years have become increasingly mediated by technologies. The analysis is grounded in the theory of social practice. Research material consists of written essays collected from 25 students at the University of Jyväskylä, Finland, in 2013. Results show that paper as material is considered suitable and adaptive to numerous reading purposes and bodily positions, while regarding the screen the places and positions of reading are viewed as more limited due to the material boundary conditions presented by devices. Students describe handwriting as a more flexible and relaxed bodily practice than typing, although the worsening skills of handwriting are recognized too. Skills and competences turned out to be less decisive factors than materials and images when trying to explain the differences in reading and writing practices when a paper/pen is compared with a keyboard/screen. Finally, the study argues that digital reading writing interfaces do not determine the ways we read and write as strongly as previously suggested.